2012
DOI: 10.1155/2012/681328
|View full text |Cite
|
Sign up to set email alerts
|

Toona sinensisLeaf Aqueous Extract Improves the Functions of Sperm and Testes via Regulating Testicular Proteins in Rats under Oxidative Stress

Abstract: Toona sinensis leaf (TSL) is commonly used as a vegetable and in spice in Asia. In this study, feeding with aqueous extract of TSL (TSL-A) alleviated oxidative stress and recovered the motility and functions of sperm in rats under oxidative stress. Protein expressions in testes identified by proteomic analysis and verified by Western blot demonstrated that TSL-A not only downregulated the level of glutathione transferase mu6 (antioxidant system), heat shock protein 90 kDa-β (protein misfolding repairing system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…In 2005, results of Poon et al (2005) suggested that TSL could increase the motility of sperms via suppressing steroidogenesis, cAMP-PKA pathway and steroidogenic enzymes activities in normal mouse leydig cells. Furthermore, another paper also reported TSL could improves the functions of sperm and testes via downregulation of glutathione transferase mu6, heat shock protein 90 kDa-␤, cofilin 2 and cyclophilin A, whereas up-regulation of crease3-hydroxy-3-methylglutaryl-coenzyme A synthase 2, heat shock glycoprotein 96, and pancreatic trypsin 1 (Yu et al, 2012b). These findings suggest T. sinensis is a valuable agent for men to ameliorate functions of sperm and testes under oxidative stress.…”
Section: Male Reproductive System Protectionmentioning
confidence: 87%
“…In 2005, results of Poon et al (2005) suggested that TSL could increase the motility of sperms via suppressing steroidogenesis, cAMP-PKA pathway and steroidogenic enzymes activities in normal mouse leydig cells. Furthermore, another paper also reported TSL could improves the functions of sperm and testes via downregulation of glutathione transferase mu6, heat shock protein 90 kDa-␤, cofilin 2 and cyclophilin A, whereas up-regulation of crease3-hydroxy-3-methylglutaryl-coenzyme A synthase 2, heat shock glycoprotein 96, and pancreatic trypsin 1 (Yu et al, 2012b). These findings suggest T. sinensis is a valuable agent for men to ameliorate functions of sperm and testes under oxidative stress.…”
Section: Male Reproductive System Protectionmentioning
confidence: 87%
“…While the underlying pharmacological mechanisms of TS remain unclear, various biological activities of TS leaf extracts have been reported. Recent scientific investigations demonstrated that aqueous leaf extracts of TS possess a variety of biological activities, including antioxidant, anticancer, anti-inflammation, antidiabetes, and antiangiogenesis effects, as well as the ability to inhibit Leydig cell steroidogenesis and improve the quality and dynamic activity of human sperm [ 15 18 ]. The safety levels and nontoxic characteristics of TS were evaluated using acute and subacute toxicity studies in mice and rats, and no lethal effects were found at concentrations as high as 1 g/kg body weight [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…TSL aqueous extracts repressed the ROS level, maintained the mitochondrial membrane potential (MMP) and restored sperm motility to improve sperm and testicular function under oxidative stress [96]. Studies have shown that increased levels of oxidative stress may be one of the main causes of decreased semen quality.…”
Section: Effects On the Male Reproductive Systemmentioning
confidence: 99%